Implementasi TQM terhadap Produktivitas Karyawan yang di Mediasi oleh Kepuasan Kerja pada Perusahaan Manufaktur Sepatu PT. X di Cianjur dan PT. Y di Tangerang - Jenita Maulina; Rini Mulyani Sari (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the effect of Total Quality Management (TQM) on employee productivity with job satisfaction as an intervening variable at PT. X in Cianjur and PT. Y in Tangerang. A quantitative approach was used with a survey method, with a population of 300 people and a sample of 120 respondents. The data analysis technique used is path analysis using SPSS version 25 software. The research results show that TQM has a direct influence on employee productivity, job satisfaction also has an influence on employee productivity, and TQM has an indirect positive influence on employee productivity through satisfaction. work as an intervening variable. In conclusion, this research highlights the importance of implementing TQM and increasing job satisfaction as a strategy to increase employee productivity in the shoe industry. Keywords: Employee Productivity, Job Satisfaction, TQM